The Influence Of Distribution Channels In Increasing Sales Volume At PT Avian Tbk - Tje moch giral prayoga; Al Hasin (International Journal of Economics, Business and Innovation Research, 2026)
This research has the main objective of analyzing the influence of distribution channels in increasing sales volume at PT Avian TBK, marketing channel efficiency and marketing channel reach. The focus of this research is to understand how each of these factors contributes to sales volume. This research uses a survey method to collect data in the field, where the research location is chosen purposively, namely based on certain considerations that are relevant to the research topic. Sampling was carried out using the Slovin formula, which aims to determine the number of samples proportional to the population level. From the calculation results, the sample used in this research consisted of 179 respondents, all of whom were avian paint business actors who were the object of research. To analyze the data collected. The results of this research shows that of the two, marketing channel efficiency has significant and real influence on the sales volume of avian paint. Apart from the efficiency of marketing channels, the reach of marketing channels also influences the sales volume of avian paint